From Smallholder Rubber Income to the Schoolfonds: Fiscal Mechanisms and the Development of Schooling in Kuantan, Riau (1916-1932) - Sabrina Sabrina; Nur Aini Setiawati (Diakronika, 2026)
This article examines the relationship between smallholder rubber cultivation, the schoolfonds (a locally administered education fund financed through compulsory contributions), and education in Kuantan during 1916–1932, highlighting the local economy as a key factor in shaping educational development. It aims to analyze and reconstruct the trajectory of educational development and sustainability in Kuantan through the schoolfonds taxation mechanism. The study employs the historical method, including heuristics, source criticism, interpretation, and historiography. The findings show that the economic opening of Kuantan through smallholder rubber plantations generated complex administrative demands, which contributed to the establishment of the schoolfonds in 1916. The schoolfonds was created to finance the overall provision of education in the Onderafdeeling Kuantan (an administrative division under afdeeling, headed by a controleur). However, the global economic crisis of the early 1930s led to a sharp decline in rubber prices and exports, directly reducing local incomes and schoolfonds revenues. This downturn resulted in the contraction of educational facilities and funding, necessitating austerity in the allocation of schoolfonds. This study argues that, structurally, the expansion and sustainability of education in Kuantan rested upon the material foundation of rubber-generated surplus, converted into public funding through a fiscal mechanism (schoolfonds). More importantly, this study contributes to a rethinking of the history of educational financing outside Java by demonstrating that educational development in Kuantan was not solely the result of colonial state intervention (top-down), but was also shaped by the stability of the smallholder rubber economy and the operation of local fiscal mechanisms.